Retrospective study of the outcome of primary repair of arteriovenous fistula (AVF) aneurysm and pseudoaneurysm in secondary hospital setting - Ong, Xin Zen; Ling, Li Fan; Philip Ding Hsin Loong,; Chong, Kar Hon; Goh, Neng Xiang; Kang, Jo An; Umasangar Ramasamy, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Aneurysms and pseudoaneurysm are commonly encountered with arteriovenous vascular access for haemodialysis. They are difficult complications to manage. Due to the limited number of vascular centers available, patients were unable to seek treatment until further complications arise. The technique of partial aneurysmectomy and primary repair was adopted as the method of repair in this study. A total of 20 cases underwent the surgery from 2019 to 2020. Among the 20 cases, one patient had two pseudoaneurysms at different location which requires her to undergo the procedure twice. The successful cannulation rate post repair was 70% whereas the overall complication rate was 35% which might be attributed to the small sample size. Overall, this study demonstrated that AVF aneurysm and pseudoaneurysm can be safely treated with this approach and can be done effectively in non-vascular centers by general surgeons.